Keragaman Fenotipe dan Heritabilitas Kedelai (Glycine max [L.] Merril) Generasi F6 Hasil Persilangan Wilis X Mlg2521 - Kusuma, Ridwan; Sa?diyah, Nyimas; Nurmiaty, Yayuk (Politeknik Negeri Lampung., 2016)
Soybean consumption here in Indonesia continues to increase each year that is notaccompanied by an increase in soybean production. One way to increase soybeanproduction by using improved varieties. The purpose of this study were (1) Estimating thevalue of the diversity of phenotypes soy F6 generations from crosses between Wilis x Mlg2521,(2) Estimating the heritability estimates soybean F6 generations from crosses Wilis x Mlg2521,(3) Know the numbers expectation of F6 generation crosses Wilis x Mlg2521. The researchwas conducted from March 2014 until June 2014 at the Land Lab Lampung StatePolytechnic and observations made in Laboratory of Seed and Plant Breeding, University ofLampung. Soybean seeds used were F6 generation zuriat from Wilis x Mlg2521, Wilis andMlg2521. The treatment laid out in a randomized block design, 2 replications. The resultsshowed that (1) The diversity of phenotypes population F6 for characters date of flowering,harvesting age, plant height, number of productive branches, total number of pods plant,weight of 100 grains, grain weight plant and number of seeds plant including all the broadcriteria, (2) The value of heritability estimates the population F6 for characters date offlowering, harvesting age, plant height, number of productive branches, total number ofpods plant, weight of 100 grains, grain weight per plant and number of seeds plantbelonging to the high criteria, (3) Number expectations of the population F6 is 7-64-1-8 and7-64-1-3.Keywords: heritability, phenotypic variance, soybean